2013
DOI: 10.3109/14992027.2013.796532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the presence of auditory neuropathy spectrum disorder (ANSD) on outcomes of children at three years of age

Abstract: Objective To determine the influence of the presence of auditory neuropathy spectrum disorder (ANSD) on speech, language, and psycho-social development of children at three years of age. Design A population-based, longitudinal study was performed on outcomes of children with hearing impairment (LOCHI) in Australia. The demographic characteristics of the children were described, and their developmental outcomes were evaluated at three years of age. Performance of children with ANSD was compared with that of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
(73 reference statements)
6
31
0
Order By: Relevance
“…Conversely, the association between premature birth and achievement of open-set speech perception was positive. Additional disabilities may affect speech perception outcomes of pediatric CI recipients regardless of etiology of hearing loss [8, 12, 18, 19, 4649]. The present study indicates that prelingual deafness and CNS abnormalities had a negative association with the outcome.…”
Section: Discussionmentioning
confidence: 60%
“…Conversely, the association between premature birth and achievement of open-set speech perception was positive. Additional disabilities may affect speech perception outcomes of pediatric CI recipients regardless of etiology of hearing loss [8, 12, 18, 19, 4649]. The present study indicates that prelingual deafness and CNS abnormalities had a negative association with the outcome.…”
Section: Discussionmentioning
confidence: 60%
“…This increased incidence of additional disabilities is typically reported for children with ANSD [46].…”
Section: Discussionmentioning
confidence: 68%
“…Two separate Nigerian studies indicated a prevalence of 4.9% in a sample of children diagnosed with SNHL [45] and 13.5% in a cohort of children with severe-profound hearing loss [44]. Hyperbilirubinemia has been associated as the most commonly reported risk factor for ANSD, varying between 30 to 70% [38,[46][47][48]. The current study had 50% of ANSD cases presenting with hyperbilirubinemia as a risk factor similar to a recent report from South Africa in which half of the ANSD cases (n=5/10) also presented with hyperbilirubinemia [24].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, solely amplifying sound is not expected to improve auditory signalling, whereas the strong electrical stimulus of a cochlear implant can synchronously activate SGNs even in cases of impaired auditory nerve function 133 . However, although the outcome of auditory neuropathy in children with cochlear implants can indeed be similar to those with hearing impairment owing to other aetiologies, it does not seem to be substantially better than that of auditory neuro pathy fitted with hearing aids 134,135 . Of course, it is quite possible that the patients with auditory neuro pathy who were fitted with cochlear implants were more severely affected and would have had a worse outcome with hearing aids.…”
Section: Uncertainties In Outcomesmentioning
confidence: 99%